Modifikasi Media Pada Pembelajaran PJOK: Desain Faktorial 2x2 Untuk Meningkatkan Hasil Belajar Berbasis Motivasi - Komalasari, Mutiara; Kurniawan, Edi; Soemardiawan; Muhaimin, Ali (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
Physical Education (PJOK) learning in elementary schools often produces uneven results when relying on conventional media. This study aimed to test whether modified learning media improve learning outcomes compared to traditional media, assess the influence of learning motivation, and examine the interaction between the two. A 2×2 factorial quasi-experimental design was implemented with fifth-grade students, with two learning conditions (modified vs. conventional media) and two levels of motivation (high vs. low). Learning outcomes were comprehensively measured across cognitive (multiple-choice test), psychomotor (performance rubric), and affective (observation) domains, while motivation was measured using a questionnaire. A two-way ANOVA revealed a significant main effect of media: the modified media group outperformed the conventional group in all three domains. The main impact of motivation was also substantial, with highly motivated students achieving better. There was a media × motivation interaction: the superiority of modified media was most pronounced among highly motivated students, while providing a buffering effect for lower-motivated students. The findings were supported by game-based task design, audiovisual modeling, developmentally appropriate tool adaptations, teacher training, and safety procedures. It is concluded that when well designed and implemented, modified media is practical and feasible to improve the quality of PJOK learning in elementary schools.